Profil Pembelajaran Berdiferensiasi Pada Pelajaran Matematika - A, Komarudin (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
One of the essences developed in independent learning is differentiated learning. Through differentiated learning, the various needs of students can be facilitated so that results can be achieved according to needs at the end of the learning process. This research aims to explore and describe differentiated learning. This research is a type of descriptive research with a qualitative approach. The research subjects are articles selected using purposive techniques. The data collection method used is documentation with instruments in the form of articles from scientific journals. The data analysis method consists of three stages, namely: data reduction, data presentation, and conclusion. The results of this research are that differentiated learning is learning that facilitates freedom which facilitates different needs with different processes and also for different achievements. With the suggestions that can be conveyed, it is hoped that teachers can fully and comprehensively understand the essence of differentiated learning so that they can apply it optimally in the learning process when teachers teach in the class. Keywords: learning, differentiate